Appreciative Leadership and Employee Well-Being in Everyday Working Life. (February 2014) - Stocker, Désirée; Jacobshagen, Nicola; Krings, Rabea; Pfister, Isabel B.; Semmer, Norbert K.
This study examines the relationship between appreciative behavior and employee well-being on a daily basis. The theoretical rationale of our approach is based in leadership concepts emphasizing the relational aspect of leadership, and, more generally, in a framework that emphasizes the central role of threats, or boosts, to self-esteem (i.e., the concept of "Stress-as-Offense-to-Self" [SOS]). Qualitative and quantitative data of 139 employees working in different occupations were assessed during five consecutive workdays. First, based on event-sampling of appreciative situations, the nature of appreciative situations from the perspective of the employees, as it manifests itself in daily episodes, was examined. Simple praise and gratitude were the most frequent types of appreciative behavior reported. Besides leaders, customers and co-workers were frequent sources of appreciation as well. Second, the intra-individual effects of daily experiences of appreciation on employee well-being at the end of work were analyzed. Multi-level random coefficient modeling showed that daily appreciation by all sources significantly predicted serenity (i.e., a low-arousal / high pleasure type of well-being) at the end of work. As serenity is likely to affect recovery, which, in turn, may affect health and performance, our findings show that for leaders, but not only for leaders, displaying elementary appreciative behavior is a simple but important tool for enhancing employee health and well-being.